Laporan Kasus: Penanganan Nyeri Neuropati diabetik Dengan Menggunakan Terapi Musik - Mohammad Shiddiq Suryadi; Atika Jatimi; Qomaruddin Sudindi (Indonesian Health Science Journal, 2023)
Introduction; Diabetic neuropathy pain is a complication that is often experienced by diabetes mellitus sufferers who complain of pain in the extremities due to increased blood glucose levels. Objective; to describe the effectiveness of providing music therapy to clients experiencing diabetic neuropathy pain. Method; The implementation of this case study uses a nursing process approach through five stages, namely assessment, establishing a nursing diagnosis, developing interventions, implementing nursing plans and evaluating the results of actions. Patients were selected using a purposive sampling method, with action carried out in the community. Results; After applying music therapy three times, clients who experienced diabetic neuropathy pain experienced an improvement in their health condition which was marked by a decrease in pain. Conclusion; The results of the evaluation after implementing the action on a client diagnosed with diabetes mellitus who complained of diabetic neuropathy pain showed that the nursing problem was resolved.